"A picture tells a thousand words" smartphone-based secure clinical image transfer improves compliance in open fracture management. Issue 7 (July 2019) - Li, Martin Ka-Ho; Howard, Daniel P.; King, Richard
Highlights: Confidential clinical photography of wounds of patients with open fractures has been difficult without a convenient app. A confidential clinical photography app significantly improves compliance of clinical photography in patients with open fractures. The quality of clinical afforded by the app is good when graded for context, comprehensiveness and clarity of wounds. Abstract: Background: BOAST (British Orthopaedic Association Standards for Trauma) and NICE (National Institute of Clinical Excellence) guidelines recommend clinical photography of all open fractures on admission and at key stages of patient care for objective wound documentation and to avoid repeated examination. Recording and handling photographs in a compliant and confidential manner in the setting of acute trauma management can prove challenging. To facilitate clinical photography at our Major Trauma Centre (MTC) institution, a smartphone-based Secure Clinical Image Transfer (SCIT) app was introduced and integrated with the existing clinical photography database to allow clinicians to take photographs, which are saved directly to patient records. Objectives: To compare rates of information governance (IG)-compliant clinical photography of wounds of patients with open fractures before and after introduction of departmental smartphones loaded with the clinical photography app SCIT. Methods: Admission lists were inspected retrospectively for patients admitted with open fractures between August and October 2016, before SCIT was introduced. The Trust clinical photography database was searched for corresponding patient images and where present, graded out of three for clarity, comprehensiveness and context. The procedure was repeated prospectively from August to October 2017 after rollout of SCIT. The uptake and quality of photography were statistically compared (Fisher's exact test, significance level p < 0.05). Results: 42 open fractures were identified in the 2016 period and 40 in the 2017 period. None of the 42 patients in the 2016 cohort had records of IG-compliant clinical photography on admission. 16 of 40 patients in the 2017 cohort had IG-compliant clinical photography on admission. This was statistically significant (p < 0.0001). 5 of 42 patients in the 2016 cohort and 8 of 40 patients in the 2017 cohort had photographs after first debridement. This was statistically insignificant (p = 0.375). All five photographs in the 2016 cohort scored 3/3. 18 of 21 photographs in the 2017 cohort scored 3/3, one scored 2/3 and two scored 1/3. Conclusions: Integrating commonplace smartphone technology with a secure platform for taking and storing photographs can improve rates of IG-compliant clinical photography of open fractures. This may improve documentation, communication and patient care.